Neonatal mortality in the Maribor region (1997–2008): Umrljivost novorojenčkov na območju Maribora (1997-2008) - Burja, Silva; Treiber, Milena; Tekauc-Golob, Andreja; Takač, Iztok; Hajdinjak, Dušanka; Gajšek-Marchetti, Marijana; Mičetić-Turk, Dušica (Acta Medico-Biotechnica, 2021)
Purpose: To provide a summary of neonatal mortality data for a group of 24,044 live births in the Maribor Department of Perinatology between 1997 and 2008.Methods: The National Perinatal Informational System (NPIS) cohort files for 1997–2008 were used for this study. Data are presented using cohorts based on dates of birth and death. The University Clinical Center serves the population of northeastern Slovenia, with 24,044 live births in this 12-year period. Yearly cohorts of neonatal deaths were analyzed by gestational age (GA) distribution, birth weight (BW) distribution, age at death, and cause of death.Results: The average neonatal mortality rate in the 12-year investigated group was 2.2 per 1000 live births with a GA of 28-42 weeks and 4.7 per 1000 live births with a GA of 22-42 weeks. The smallest group, with an extremely low birth weight (ELBW; 2500 g accounted for approximately 20% of all neonatal deaths. The largest percentage of neonatal deaths was deaths due to immaturity, and represented 54% of all reported deaths during the investigated period.Conclusion: Oscillations in neonatal mortality rates during the 12 years first occurred in 1997-2005 in direct connection with the number of extremely premature newborns. In the last 4 years of the 12 years we observed a new and better quality indicator, i.e., a lower neonatal mortality rate in spite of the increased preterm delivery rate. Analysis of quality indicators in perinatology should be part of routine clinical care.
Keywords: neonatal mortality; gestational age; birth weight; Maribor